Transforming Hospital Environments: The Role of Sound Detection - Chinmay Revansidhha Pogul; Kazi Kutubuddin Sayyad Liyakat; Heena T Shaikh (International Journal of Electrical and Communication Engineering Technology, 2026)
Hospitals are sanctuaries of healing, yet they are often paradoxically exposed to a pervasive, often underestimated threat: excessive noise. While internal hospital sounds pose their own challenges, the impact of external sounds – traffic, construction, sirens, and urban clamor – can profoundly compromise patient safety, recovery, and overall well-being. This article explores the critical role of advanced sound detection systems in mitigating this external acoustic intrusion, leveraging technology to create a truly restorative environment for patients. For patients recovering from illness or surgery, a peaceful environment is not merely a luxury but a clinical necessity. External noise disrupts this vital serenity in several ways. An advanced sound detection system in a hospital setting is not simply a decibel meter; it's a sophisticated network designed to proactively identify, classify, and manage external acoustic threats. The deployment of such a system directly translates into tangible improvements in patient safety and quality of care. Unlike basic decibel meters, advanced sound detection systems employed in hospitals are intelligent, network-enabled solutions designed for real-time monitoring and analysis of the acoustic environment, with a specific focus on external sound sources. The ability to identify, quantify, and respond specifically to external acoustic threats allows healthcare facilities to cultivate a genuinely tranquil healing environment. This proactive approach not only enhances patient comfort and satisfaction but, more importantly, directly contributes to faster recoveries, reduced complications, and ultimately, safer patient outcomes.
Keywords: Environment; External Sound; Hospital; Safety; Sound; patient; sensors